Potential of Meat Substitutes for Climate Change Mitigation and Improved Human Health in High-Income Markets - Ritchie, Hannah; Reay, David S.; Higgins, Peter (Frontiers in Sustainable Food Systems, 2018)
The global food system contributes approximately one-quarter of greenhouse gas (GHG) emissions, with these dominated by the livestock sector. The projected increase in livestock demand is likely to undermine efforts to keep global average warming below a 2°C target. A carbon tax is often proposed as the preferred demand-side mechanism for reduced meat consumption. Previous studies, however, suggest that while this could prove successful in reducing net global emissions, it may worsen nutritional standards in lowest-income nations. An alternative market mechanism which may simultaneously reduce GHG emissions and improve health at all income levels is a reduction in the price of meat substitute products (meat-free proteins with particular nutritional and aesthetic similarities to meat). Using a combined ecological and health modelling approach, we project the associated GHG savings and health benefits associated with a stepwise reduction in the price of meat substitute products. Utilising food demand elasticities, we quantify the substitution of meat commodities across a range of social acceptability scenarios. Our results show that meat substitute products-integrated within a 'flexitarian' approach (primarily vegetarian but occasionally eating meat and fish)-have a large potential for reducing GHG emissions (up to 583MtCO2e per year) and improving nutritional outcomes (up to 52,700 premature deaths avoided per year). However, this capacity is strongly dependent on a combination of price reductions and improved social acceptability of this product group; therefore both will be essential.